Aksi Sosial Real Care Bagi Masyrakat Terdampak Malnutrisi di Kabupaten Asmat - Fransiskus Irwan Widjaja; Daniel Ginting; Ronald Sianipar; Sabar Hutagalung; Winson Simmamora; Benteng MM Purba; Ardi Lahagu; Evan Dongoran; Candra Gunawan Marisi (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2018)
Papua, one of the richest provinces in Indonesia, contributes the most taxes, but Papua is one of the poorest regions in Indonesia with a low Human Development index. Indicators can be seen from the level of Education and the level of Health. One of the biggest humanitarian disasters in Papua's history in 2018 was the case of malnutrition in Asmat District, in Nakai village, Pulau Tiga District, and Agats City. The lack of volunteers and a large number of victims moved the PKM STT Real Batam in collaboration with volunteer doctors from GBI Myhome Tanjungpinang to go directly to help deal with malnutrition and other health treatments, as well as serve the community. The implementation method in this community service program, namely direct treatment and providing counseling, assistance to families who pay less attention to health. From the results of the evaluation with the PKM team, going directly to see the conditions and mentoring activities is very useful because, in addition to knowing the level of public health and helping to provide vitamins, vitamins, and other supplements, the theme also provides counseling, helps overcome social problems affected and their handling. Abstrak Papua, salah satu propinsi terkaya di Indonesia yang menyumbang pajak terbesar, tetapi Papua adalah salah satu daerah termiskin di Indonesia dengan indeks Pembangunan manusia yang rendah. Indikator dapat dilihat dari tingkat Pendidikan dan tingkat Kesehatan. Salah satu bencana kemanusiaan yang terbesar dalam sejarah Papua di tahun 2018 adalah kasus gizi buruk di Kab Asmat, di kampung Nakai Distrik Pulau tiga dan Kota Agats. Minimnya relawan dan banyakknya korban menggerakkan PKM STT Real Batam yang menggandeng dokter relawan dari GBI Myhome Tanjungpinang untuk terjun langsung untuk membantu penanganan gizi buruk dan pengobatan kesehatan lainnya, serta melayani masyarakat. Metode pelaksanaan pada program pengabdian masyarakat ini, yaitu pengobatan langsung dan memberi penyuluhan, pendampingan keluarga keluarga yang kurang memperhatikan Kesehatan. Dari hasil evaluasi dengan team PKM, turun langsung melihat kondisi dan pendampingan kegiatan sangat berguna karena selain mengetahui tingkat Kesehatan masyarakat dan membantu memberi vitamin vitamin dan supplement lainnya, tema juga memberi penyuluhan, membantu mengatasi masalah masalah social yang terdampak dan penanganannya.